Androgen Deprivation Therapy in the Treatment of Advanced Prostate Cancer - Perlmutter, Mark A (MedReviews, LLC, 2007)
This article reviews the issues and controversies relevant to the treatment of advanced prostate cancer with androgen deprivation therapy. Initially, diethylstilbestrol was used for achieving androgen deprivation, but was replaced by luteinizing hormone-releasing hormone (LHRH). Adverse events associated with LHRH agonists include the flare phenomenon, hot flashes, loss of libido, erectile dysfunction, depression, muscle wasting, anemia, and osteoporosis. Intermittent therapy has been advocated to reduce morbidity of treatment. The addition of an antiandrogen provides maximum androgen blockade. There remains controversy regarding the timing of the addition of an antiandrogen. Secondary hormonal therapies include antiandrogens, adrenal androgen inhibitors, and estrogens.